2021
DOI: 10.1371/journal.pone.0259040
|View full text |Cite
|
Sign up to set email alerts
|

Stuck in a lockdown: Dreams, bad dreams, nightmares, and their relationship to stress, depression and anxiety during the COVID-19 pandemic

Abstract: Background An upsurge in dream and nightmare frequency has been noted since the beginning of the COVID-19 pandemic and research shows increases in levels of stress, depression and anxiety during this time. Growing evidence suggests that dream content has a bi-directional relationship with psychopathology, and that dreams react to new, personally significant and emotional experiences. The first lockdown experience was an acute event, characterized by a combination of several unprecedent factors (new pandemic, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
58
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(61 citation statements)
references
References 93 publications
3
58
0
Order By: Relevance
“…Previous studies have highlighted that the pandemic had an influence on dream and nightmare contents [ 18 , 25 , 26 , 27 , 28 , 29 , 30 ]. Here, we found that, despite a substantial stability in the most frequently reported dream themes, only the frequency of specific dream contents was reduced in PL.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have highlighted that the pandemic had an influence on dream and nightmare contents [ 18 , 25 , 26 , 27 , 28 , 29 , 30 ]. Here, we found that, despite a substantial stability in the most frequently reported dream themes, only the frequency of specific dream contents was reduced in PL.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is plausible that the selective decreased frequency of specific dream contents at PL observed in the present study reflects a reduced emotional charge of specific concerns and personal meanings associated with the experience of home confinement during TL. Indeed, two of these themes (being frozen with fright, being half awake and paralyzed in bed) can be considered the expression of a general topic of paralysis [ 30 ] associated with a fearful condition: one (being isolated/locked up/shut down) seems strictly coherent with the TL experience, one (war) appears evocative of an exceptional and dangerous context, and three (being in crowded places, travelling, loved ones) concern objects and experiences that were strongly limited during TL. Overall, such themes may represent specific lockdown-related topics.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As Covid-19-related worries were not related to dream recall frequency, it is very likely that the subjectively reported increases in dream recall frequency due to the pandemic ( Fränkl et al, 2021 ; Guerrero-Gomez et al, 2021 ; Schredl & Bulkeley, 2020 ; Solomonova et al, 2021 ) might not be explained by direct effects of the pandemic itself on dream life but by indirect effects, for example, changes in sleep behavior due to lock-downs ( Gorgoni et al, 2021 ; Scarpelli et al, 2021 ), e.g., home schooling and home office increased sleep duration in some parts of the population ( Bottary et al, 2020 ) whereas, on the other hand, sleep problems including more frequent nocturnal awakenings were also reported more often during the pandemic ( Dal Santo et al, 2021 ). That is, longer sleep duration ( Schredl & Fulda, 2005 ), on the one hand, and insomnia and frequent nocturnal awakenings ( Schredl et al, 1998 ), on the other hand, are related with higher dream recall frequency.…”
Section: Discussionmentioning
confidence: 99%
“…The main objective of the present study was to investigate the relationship between the Big Five personality factors, dream recall frequency, and lucid dream frequency in a new and independent sample. However, as the survey was carried out during the Covid-19 pandemic, we had the opportunity to explore whether the presence and intensity of Covid-19-related anxiety is related to dream recall frequency and/or lucid dream frequency as a substantial number of studies ( Fränkl et al, 2021 ; Guerrero-Gomez et al, 2021 ; Schredl & Bulkeley, 2020 ; Solomonova et al, 2021 ) reported an increased dream recall frequency due to the pandemic in a substantial percentage of the population. For focusing on the main objective of the study, we included this COVID-19 related variable in the regression analysis in order to control for possible confounding effects.…”
mentioning
confidence: 99%